Comparing C-peptide and HbA1c levels in obese patients with and without type 2 diabetes - Sridevi, N.; Chowdeswari, N.; Navaneeta Lakshmi, A.; Madhusudhan, P.; Kirmani, N.; Anil, Rakesh; Kumar, Shyam Sundar (International Journal of Research in Medical Sciences, 2026)
Background: Diabetes mellitus (DM) is a chronic metabolic disorder characterized by either insufficient insulin production by the pancreas or the body’s inability to utilize it. HbA1c level of 6.5% was recommended for diagnosing diabetes. C-peptide is a byproduct of insulin synthesis has been widely studied as a diagnostic biomarker for DM. Obesity is a major risk factor for the development of type 2 DM (T2DM) and is associated with insulin resistance. With the increasing global burden of obesity and diabetes, our study investigates the relationship between HbA1c and C-peptide levels in obese individuals with and without diabetes. Objectives were to assess and compare HbA1c and C-peptide levels among obese individuals with diabetes and without diabetes and to evaluate the correlation between these parameters within each group. Methods: This study was included 30 obese diabetic and 30 obese non-diabetic participants recruited over 3 months. Blood samples were collected for estimating HbA1c and C-peptide. Ethical approval was obtained prior to the study. Data were analyzed using Jamovi software. Results: HbA1c and C-peptide levels were significantly higher in obese individuals with diabetes compared to non-diabetic obese controls (p<0.001). A strong positive correlation was observed between HbA1c and C-peptide levels in both groups, with a stronger association in diabetics (r=0.94) compared to non-diabetics (r=0.88); both correlations were statistically significant. Conclusions: Higher levels and strong positive correlation between HbA1c and C-peptide-especially in diabetics-suggests increased insulin secretion in response to poor glycemic control and insulin resistance.